2019
DOI: 10.1111/jdi.13124
|View full text |Cite
|
Sign up to set email alerts
|

Wingless‐type MMTV integration site family member 5a is a key inhibitor of islet stellate cells activation

Abstract: Aims/Introduction Type 2 diabetes mellitus is a chronic metabolic disorder characterized by islet β‐cell dysfunction, which might result from the activation of islet stellate cells (ISCs). Our recent study showed that a specific population of ISCs is prone to be activated in type 2 diabetes mellitus accompanied by reduced secretion of insulin. The wingless‐type MMTV integration site family member 5a (Wnt5a)/frizzled‐5 signaling pathway might play an important role in this process. The present study aimed to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
4
3
0
Order By: Relevance
“…Our previous studies have confirmed the presence of stellate cells within the islets (ISCs), which are identical in the expression of retinoid-containing fat droplets [51,52,53,54,55]. A loss of oil red O-stained fat droplets was associated with the activation of diabetic ISCs, and we speculate whether the transfer of lipid droplets from the inside to the outside of the ISCs leads to local fat deposition and the inhibition of normal β-cell function.…”
Section: Discussionsupporting
confidence: 66%
“…Our previous studies have confirmed the presence of stellate cells within the islets (ISCs), which are identical in the expression of retinoid-containing fat droplets [51,52,53,54,55]. A loss of oil red O-stained fat droplets was associated with the activation of diabetic ISCs, and we speculate whether the transfer of lipid droplets from the inside to the outside of the ISCs leads to local fat deposition and the inhibition of normal β-cell function.…”
Section: Discussionsupporting
confidence: 66%
“…These results indicate that dietary high-fat supplementation for 28 weeks induced a positive relationship between α -SMA expression and ISCs in obese rats. These observations are consistent with previous studies that showed in diabetic environment, the activation of ISCs leads to increase in ISC-derived secretory products and influences islet function [ 5 , 6 , 19 , 26 ]. Our group previously found that ISCs were similar but not identical to pancreatic stellate cells (PSCs) [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our previous studies showed that stellate cells in islets, named islet stellate cells (ISCs), which are rich in LDs and positive for desmin and GFAP expression under physiological conditions, proliferate fast and generate the fibrotic extracellular matrix (ECM) when activated by various pathological stimuli. Furthermore, ISCs show specific expression of α -smooth muscle actin ( α -SMA), and secretion of collagen I (Col I), fibronectin (FN), and other ECM components that induce the formation of islet fibrosis with a parallel disappearance of LDs, consequently leading to T2DM [ 5 , 6 ]. However, the underlying pathogenesis and mechanism of ISCs activation have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm Min6 cell proliferation, a 5-ethynyl-2′-deoxyuridine (EdU) assay was used for analysis as described previously [18]. Groups of 2 × 10 4 Min6 cells were incubated in the absence or presence of exogenous Wnt5a (0.05 μg/ml) for 48 h before labelling with 10 μM EdU for 4 h at 37°C, and cell proliferation was assessed by colorimetric quantification of EdU incorporation into cellular DNA [18].…”
Section: Determination Of Cell Proliferationmentioning
confidence: 99%
“…A clinical study by our team showed that the serum Wnt5a level was significantly decreased in newly diagnosed T2DM patients compared with normal controls [17]. In addition, exogenous Wnt5a inhibited the activation of ISCs and increased insulin secretion from islets [7,18]. e FoxO1 and Pdx1-Glut2insulin pathway plays an important role in glucosestimulated insulin secretion (GSIS) [19].…”
Section: Introductionmentioning
confidence: 99%